2020
DOI: 10.1186/s12882-020-1709-z
|View full text |Cite
|
Sign up to set email alerts
|

The incidence, risk factors, and long-term outcomes of acute kidney injury in hospitalized diabetic ketoacidosis patients

Abstract: Background Emerging evidence has demonstrated that acute kidney injury (AKI) is an important risk factor associated with increased morbidity and mortality in diabetic ketoacidosis (DKA) patients. The current study aimed to investigate the incidence rate, risk factors, long-term renal outcomes, and mortality in DKA patients with AKI. Methods A total of 179 patients diagnosed with DKA at Sun Yat-sen Memorial Hospital from January 2012 to January 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 38 publications
(53 reference statements)
5
40
2
5
Order By: Relevance
“…Our study demonstrated that the incidence of AKI from DKA patients in our study is 41.3% according to 2012 KDIGO during the ICU stay. The incidence is slightly lower than is reported in previously published studies [8,9,11], but it is also higher than the general patients' comparing with DKA patients. The HLOS, hospital mortality, and use of mechanical ventilation in the AKI group were much higher than the non-AKI group, which indicated adverse effects and a considerable economic burden for patients developing AKI.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…Our study demonstrated that the incidence of AKI from DKA patients in our study is 41.3% according to 2012 KDIGO during the ICU stay. The incidence is slightly lower than is reported in previously published studies [8,9,11], but it is also higher than the general patients' comparing with DKA patients. The HLOS, hospital mortality, and use of mechanical ventilation in the AKI group were much higher than the non-AKI group, which indicated adverse effects and a considerable economic burden for patients developing AKI.…”
Section: Discussioncontrasting
confidence: 65%
“…In the multivariate regression model, T2DM patients were associated with a more than 2.5-fold increase in the odds of DKA-AKI than T1DM patients. Patients with T2DM are mostly older and with a higher percentage of being overweight; increasing age [9] and obesity [20] are associated with AKI, which could be one explanation of our result. Univariable regression analysis showed that older age is significantly associated with AKI (OR = 1.01, P < 0.05), which had no correlation weight (OR = 1.01, P = 0.06).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Multiple risk factors contribute to the development of acute kidney injury. Acute kidney injury and advanced acute kidney injury are associated with rapid progressive chronic kidney disease and mortality in patients with diabetic ketoacidosis [ 8 ]. The development of acute kidney injury, defined as acute changes in the serum creatinine level, characterizes hospitalized patients at increased risk of adverse outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%